2018
DOI: 10.12688/f1000research.15634.1
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care and its effect on risk of pregnancy induced hypertension in Lao PDR: A case-control study

Abstract: Background: Pregnancy induced hypertension (PIH) is a global public health concern as a leading cause of maternal mortality. Lao PDR has a high prevalence of PIH, but little is known about its risk factors. This study aimed to identify risk factors of PIH relating to antenatal care (ANC) in Lao PDR. Methods: This hospital-based age-matched case control study was carried out between July and December 2017 in tertiary and secondary hospitals in Lao PDR. A total of 258 pregnant women (86 hypertensive and 172 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…They reported that the majority of antenatal PIH women were primigravida, had a gestation period of 28 weeks, and had no history of multiple pregnancy or past history of medical disorders [22]. Also, these results were in line with those of Ronsmans and Campbell (2017), reporting that health care personnel were evaluated on their understanding and management methods of hypertension in pregnancy [23]. The majority of sample were primigravida and in second trimester.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…They reported that the majority of antenatal PIH women were primigravida, had a gestation period of 28 weeks, and had no history of multiple pregnancy or past history of medical disorders [22]. Also, these results were in line with those of Ronsmans and Campbell (2017), reporting that health care personnel were evaluated on their understanding and management methods of hypertension in pregnancy [23]. The majority of sample were primigravida and in second trimester.…”
Section: Resultssupporting
confidence: 67%
“…The majority of sample were primigravida and in second trimester. On other hand, these results were dissimilar to those of Phengsavanh et al (2018) research on the effect of antenatal care on risk of pregnancy induced hypertension in lao PDR [24]. Also, these results were different from those of Ramesh et al (2014), based on which the majority of the women had a history of hypertension and diabetes [25].…”
Section: Resultsmentioning
confidence: 66%
“…With adequate ANC (≥ 4 times), pregnant women would be monitored and have better pregnancy outcomes and a reduction in complications. This study is supported by study done in Thailand[17], USA[18]. Pregnancy induced hypertension is not a totally preventable disease but maternal and foetal Complication due to PIH can be halted at mild stage by quality Antenatal care with good outcome through controlling blood pressure variability.The other main exposure variable used in our study was self-reported consumption of iron and folic acid supplementation during pregnancy.…”
mentioning
confidence: 62%
“…12,13 Women with irregular antenatal care attendance are much more prone to pregnancy complications such as preeclampsia, eclampsia, and anemia besides higher adverse birth outcomes including preterm birth, low birth weight, and stillbirth. [14][15][16] The magnitude of PPH (postpartum hemorrhage), preterm labor, early neonatal death, and LBW (Low Birth Weight) complication reduced when a woman has complete adherence to ANC visit. 17 Kinds of the literatures showed that no maternal education, 11,18-23 permission to visit health facility, 18,21 less maternal exposure to the media, 20,21 long distance to health facilities, 20,22 and lack of companionship to health facility 21 were some of the factors repeatedly associated with underutilization of the recommended visits of FANC.…”
Section: Introductionmentioning
confidence: 99%